Advanced glycation end products in diabetic retinopathy and phytochemical therapy - Kang, Qingzheng; Dai, Haiyu; Jiang, Suwei; Yu, Li (Frontiers in Nutrition, 2022)
Advanced glycation end products (AGEs) are generated by the non-enzymic glycation on proteins or lipids. Diabetic retinopathy (DR) is one common complication in diabetes patients. The accumulation of AGEs in retinal cells is tightly associated with DR development. AGEs can induce the breakdown of redox balance and then cause oxidative stress in retinal cells, exerting cytopathic effects in DR progression. The interaction between AGEs and the receptor for AGE (RAGE) are involved in multiple cellular pathological alterations in retina. This review is to elucidate the pathogenetic roles of AGEs in the progression of DR, including metabolic abnormalities, lipid peroxidation, structural and functional alterations, neurodegeneration. In addition, the disorders associated with AGEs can be used as potential therapeutic targets to explore effective and safe treatments for DR. In this review, we also introduced the antioxidant phytochemicals as potential therapeutic strategies for DR treatment.